Spatial Heterogeneity of Plant Nutrients in Soils of Mysuru District, Karnataka, India - N.L. Rajesh, G.V. Gangamrutha and Pradip Dey, P.K. Basavaraja*, Saqeebulla H. Mohamed (Journal of the Indian Society of Soil Science, 2022)
Knowledge and analysis of the spatial variability of soil physicochemical properties in agricultural fields is important for implementing various precision agricultural management practices. In the current study geostatistical methods were used to investigate the spatial heterogeneity of soil chemical properties in Mysuru district of Karnataka. Based on classical statistics, research results indicated that the major nutrients viz., available nitrogen (N), phosphorus (P), potassium (K) and sulphur (S) content in surface soil varied from 38.0–602.2 kg N ha-1, 1.26–95.4 kg P2O5 ha-1, 82.0–814.0 kg K2O ha-1 and 2.13–71.6 mg S kg-1, respectively. The proportion of total variance that was spatially dependent varied from < 25% to > 75%, for pH (52%), organic carbon (OC) (50%), available N (63%), S (43%) copper (Cu) (45%), zinc (Zn) (51%) and boron (B) (44%) indicating that these variables (parameters) have a moderate spatial auto-correlation. Whereas, available P (83%) and K (82%) were strong spatial auto-correlation and suggesting that the parent material, terrain and climate are the main causes that determine spatial auto-correlation in the present study. The soil chemical properties like major nutrients had significantly higher correlations with pH, electrical conductivity (EC) and OC that mainly affected the spatial distributions and variability of soil chemical properties of Mysuru district of Karnataka.